PENGARUH JENIS UMPAN YANG BERBEDA TERHADAP HASIL TANGKAPAN KEPITING BAKAU (Scylla serrata) DENGAN MENGGUNAKAN ALAT TANGKAP BUBU - Farah Diana; Hafinuddin Hafinuddin; Muhajir Ansar (Universitas Teuku Umar, 2018)
Mangrove crab (Scylla serrata) is one of the fishery commodities that have higheconomic value. In addition, mangrove crab is one of export commodities to several countries such as United States, Europe, Australia, Japan, Hongkong,Taiwan, Singapore and South Korea. In general, the fishing activities of mangrove crabs in the general waters of many fishermen use different baits,it's just not known which bait is best for catching mangrove crabs. The purpose ofthis study is to determine the effect of using different types of bait to the mangrove crab catch by using bubu and know the type of bait that is most effective against the catching of mangrove crab. This research method used Completely Randomized Design (RAL) with three treatments and three replications: P1 = shredded fish, P2 = Shark skin bark, and P3 = Chicken head bait. The parameters in this study are the number of catches, the feed response and the water quality parameters, the results of this study indicate the number of catches P1 = 55.55%, P2 = 22.22% and P3 = 33.33%. While feed response time in this research P1 = 1.61, P2 = 12.03, and P3 = 11.74. From the results of this study showed the use of different baits have a very significant effect on the number of mangrove crabs (scilla serata). While the feedback response also shows the results are very real (Fcal> Ftab).